MICROWAVE ABSORPTION PERFORMANCE ANALYSIS OF A GLASS FIBER REINFORCED EPOXY WITH CARBON BLACK POWDER FILLER - Rahman Budihanifa, Arif
Stealth technology has an increasing impact on a country’s military prowess until today. Ever since the second world war, many countries have been studying for methods to cloak their military equipment from their enemies. United States, China, and Russia are currently among the leading countries in stealth technology development, military products such as aircrafts and vehicles are manufactured with high stealth capabilities. Efforts in stealth technology development are increasing in Indonesia with promising future prospect, as evidenced by the recent emergence of various research in the related subject. The use of Glass Fiber Reinforced Polymer (GFRP) is common for aerospace applications. Not only is GFRP easy to acquire and produced, but its performance in microwave absorbance were also adequate evidenced by several research. Moreover, adding carbon-based fillers such as carbon black are known to enhance the microwave absorbance performance. The purpose of this thesis is to test and analyze the microwave absorbance performance of a GFRP with added carbon black powder fillers. Therefore, it can be proven that carbon black can increase the GFRP’s performance as evidenced in previous research. Furthermore, This research is also aimed to determine the specimen’s configuration combination for the best performance based on three categories: Weight percentage composition, fabrication methods, and carbon black types. Weight percentage composition consisted of 2, 4, 6, and 8 wt.% determined based on parameters from various past parametric studies. The specimen’s preparation method was a hand lay-up method divided into two based on the mixing method: manual mixing and through a magnetic mixer. Two types of carbon black used: Cabot Vulcan N330 (CB1) which is commercially available in Indonesia, and TIMCAL C-Nergy Super C65 (CB2) which is commercially available outside of Indonesia. All specimens were tested through the Transmission/Reflection line method with rectangular waveguide available in the Radio Telecommunication and Microwave laboratory of Institut Teknologi Bandung, with the primary parameters analyzed being the S-parameters and reflection loss. Based on the results, it was shown that adding CB2 improved the performance of the GFRP while CB1 did not, be it the S-parameters or reflection loss. Therefore, it can be concluded that using CB2 is much preferable for future research and applications compared with CB1. For the specimen’s configuration combination with the best performance were by using either 2 wt.% or 4 wt.% of CB2 fabricated with hand lay-up and mixed with a magnetic mixer as the first alternative, with reflection losses recorded as high as -64.2 and -64.3 dB, respectively. The second alternative was to use either 2 or 4 wt.% fabricated with hand lay-up and manual mixing, with reflection losses were recorded up to -69.6 and -58.2 dB, respectively. The third alternative can be considered if CB2 was not available, by using 6 wt.% of CB1 and fabricate it with hand lay-up and mixed with a magnetic mixer, with results of reflection loss were recorded up to -51.5 dB.